Search for Gravitational Waves Associated with Gamma-Ray Bursts during the First Advanced LIGO Observing Run and Implications for the Origin of GRB 150906B - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Abernathy, M. R.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, P.; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; et al. (Iop Publishing Ltd, 2017)
We present the results of the search for gravitational waves (GWs) associated with gamma-ray bursts detected during the first observing run of the Advanced Laser Interferometer Gravitational-Wave Observatory (LIGO). We find no evidence of a GW signal for any of the 41 gamma-ray bursts for which LIGO data are available with sufficient duration. For all gamma-ray bursts, we place lower bounds on the distance to the source using the optimistic assumption that GWs with an energy of 10(-2)M(circle dot)c(2). were emitted within the 16-500 Hz band, and we find a median 90% confidence limit of 71 Mpc at 150 Hz. For the subset of 19 short/hard gamma-ray bursts, we place lower bounds on distance with a median 90% confidence limit of 90 Mpc for binary neutron star (BNS) coalescences, and 150 and 139 Mpc for neutron star-black hole coalescences with spins aligned to the orbital angular momentum and in a generic configuration, respectively. These are the highest distance limits ever achieved by GW searches. We also discuss in detail the results of the search for GWs associated with GRB 150906B, an event that was localized by the InterPlanetary Network near the local galaxy NGC 3313, which is at a luminosity distance of 54 Mpc (z = 0.0124). Assuming the gamma-ray emission is beamed with a jet half-opening angle <= 30 degrees, we exclude a BNS and a neutron star-black hole in NGC 3313 as the progenitor of this event with confidence > 99%. Further, we exclude such progenitors up to a distance of 102 Mpc and 170 Mpc, respectively.
Keywords: binaries: close; gamma-ray burst: general; gravitational waves